Arbitration and judicialization - Stone Sweet, Alec (Oñati Socio-Legal Series, 2011)
The arbitral world is at a crucial point in its historical development, poised between two conflicting conceptions of its nature, purpose, and political legitimacy. Formally, the arbitrator is an agent of the contracting parties in dispute, a creature of a discrete contract gone wrong. Yet, increasingly, arbitrators are treated as agents of a larger global community, and arbitration houses concern themselves with the general and prospective impact of important awards. In this paper, I address these questions, first, from the standpoint of delegation theory. In Part I, I introduce the basic “Principal-Agent” framework [P-A] used by social scientists to explain why actors create new institutions, and then briefly discuss how P-A has been applied to the study of courts. Part II uses delegation theory to frame discussion of arbitration as a mode of governance for transnational business and investment. In Part III, I argue that the International Center for the Settlement of Investment Disputes (ICSID) is presently in the throes of judicialization, indicators of which include the enhanced use of precedent-based argumentation and justification, the acceptance of third-party briefs, and a flirtation with proportionality balancing. Part IV focuses on the first wave of awards rendered by ICSID tribunals pursuant to Argentina’s response to the crushing economic crisis of 2000-02, wherein proportionality emerged, adapted from the jurisprudence of the Appellate Body of the World Trade Organization.